Media hype, greener pastures syndrome, and migration in Nigeria (2020)
The phenomenon of human migration has been described as a threat to resources and job distribution in Africa. It has been assumed that, apart from economic instability in Nigeria, portrayal of Europe and America, through films and Hip-Hop musical lyrics and videos, has also influenced most Nigerians to perceive migration as the only solution to their predicaments. However, extant studies are yet to empirically prove this hypothesis. Therefore, this chapter, through a content analysis, examines contents of Nigerian films and Hip-Hop music videos, as subsets of mass media discourse, with a view to establishing the nature of these contents in terms of how they could influence Nigerians’ attitude towards migration to foreign countries. Findings show that contents of Nigerian films and Hip-Hop music videos contain rhetorical discourse with persuasive effect capable of luring Nigerian youths to foreign countries. This chapter also provides justification for the enactment of framework for policy formulation for effective control of media system and illegal migration by Nigerians.